THE IMPLEMENTATION OF GUIDED INQUIRY LEARNING MODEL IN TO IMPROVE STUDENTS' ATTITUDES OF X CLASS ON FUNGI CONCEPT - Indah Wigati; Sulton Nawawi; Pipta Juliani (Al 'Ilmi : Jurnal Pendidikan MIPA, 2016)
This study aims to determine the influence of application guided inqury model in improving the students' scientific attitude in X class on the fungi concept. This research design used Non-equivalent Control Group Design with Quasi Experimental method. Implementation of research involving 72 students in one of high school at Palembang. The research instrument used is in the form of observation sheet test and questionnaire. The data were analyzed using Microsoft Excel and SPSS 15 program. The statistical results showed that the implementation of learning using guided inquiry learning model is better than Direct Intruction (DI) learning model. Inquiry learning model is guided in improving students' scientific attitude on Fungi material in X Class. Keywords: learning model, guided inquiry, scientific attitude, fungi concept